Innovative hr transformation: Career development and employee performance in the hybrid era - Nyoman Mastiani Nadra; I Wayan Basi Arjana (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study aims to explore innovative transformations in human resource management relevant to career development and employee performance improvement in organizations implementing hybrid work systems. The primary focus of this research is the integration of digital technologies such as artificial intelligence (AI), HR process automation, and dynamic career approaches that adapt to the demands of flexible work. This study uses a descriptive qualitative approach and documentation study to identify current human resource management practices in hybrid organizations. Data were obtained from academic literature, such as relevant scientific journal articles, and then analyzed using thematic analysis techniques. The study results indicate that organizations that successfully adapt to hybrid work generally implement technology- and data-driven human resource management strategies, such as automated recruitment, adaptive online training, and digital performance management systems. The implementation of these innovations contributes to higher employee engagement, sustainable career development, and overall productivity improvements. Furthermore, active employee involvement in the managerial innovation process has been shown to strengthen organizational loyalty and resilience. This study concludes that innovative transformations in human resource management are key to supporting organizational success in the hybrid work era. This approach not only improves operational efficiency but also creates sustainable value through adaptive, skilled, and actively engaged human resources